Thermodynamic Analysis of the Phase Separation during the Polymerization of a Thermoset System into a Thermoplastic Matrix. I. Effect of the Composition on the Cloud-Point Curves - Riccardi, Carmen Cristina (2004)
The cloud‐point curves of polystyrene (PS) mixed with reactive epoxy monomers based on diglycidyl ether of bisphenol A with stoichiometric amounts of 4,4′‐methylenebis(2,6‐diethylaniline) were experimentally studied. A thermodynamic analysis of the phase‐separation process in these epoxy‐modified polymers was performed that considered the composition dependence of the interaction parameter, χ(T,Φ2) (where T is the temperature and Φ2 is the volume fraction of polystyrene), and the polydispersity of both polymers. In this analysis, χ(T,Φ2) was considered the product of two functions: one depending on the temperature [D(T)] and the other depending on the composition [B(Φ2)]. For mixtures without a reaction, the cloud‐point curves showed upper critical solution temperature behavior, and the dependence of χ(T,Φ2) on the composition was determined from the threshold point, that is, the maximum cloud‐point temperature. During the isothermal reactions of mixtures with different initial PS concentrations, the dependence of χ(T,Φ2) on the composition was determined under the assumption that, at each conversion level, the D(T) contribution to the χ(T,Φ2) value had to be constant independently of the composition. For these mixtures, it was demonstrated that the changes in the chemical structure produced by the epoxy–amine reaction reduced χ(T,Φ2). This effect was more important at lower volume fractions of PS. Nevertheless, the decrease in the absolute value of the entropic contribution to the free energy of mixing was the principal driving force behind the phase‐separation process.